Interplinian effusive activity at Popocatépetl volcano, Mexico: New insights into evolution and dynamics of the plumbing system - Mangler, Martin Friedrich; Prytulak, Julie; Gisbert, Guillem; Delgado-Granados, Hugo; Petrone, Chiara Maria (Volcanica, 2019)
Effusive eruptions dominate the eruptive record of many arc volcanoes and may hold crucial information about their plumbing systems, yet they are underrepresented in geochemical and petrological studies. Here, we present whole rock major and trace element data as well as Sr–Nd–Hf isotopic compositions for 14 lava flows and four Plinian eruptions of the Popocatépetl Volcanic Complex (PVC) in the last 23.5 ka, allowing the first comprehensive geochemical characterisation of the dynamics and evolution of its plumbing system. Lavas and pumices of the PVC are andesites–dacites with a narrow compositional range showing no first-order geochemical trends in the last 23.5 ka. Trace element and isotope ratios show that PVC magmas are derived from a depleted mantle source with a component of subducted sediments. Assimilation-fractional crystallisation models show that magma compositions are modified to varying degrees by assimilation of lower and upper crust en route to the surface. In the shallow plumbing system, geochemically distinct magmas coexist and undergo extensive mixing and hybridisation, thus buffering erupted whole rock compositions. Only few flank eruptions sample more primitive magmas from deeper reservoirs that circumvented the shallow plumbing system. Some Plinian eruptions caused compositional shifts reflecting reconfigurations of the plumbing system, which also affected subsequent effusive eruptions. Our study thus shows that the geochemical variability of PVC magmas in the last 23.5 ka is dominated by crustal processes, and magma hybridisation is the primary mechanism to produce the buffered whole rock compositions of the PVC.